2015
DOI: 10.1097/dcr.0000000000000321
|View full text |Cite
|
Sign up to set email alerts
|

Size and Distribution of Lymph Nodes in Rectal Cancer Resection Specimens

Abstract: To ensure accurate nodal staging of rectal cancer, both resection and subsequent pathological evaluation should focus on the mesorectum in close proximity to the tumor and along the superior rectal artery. Small lymph nodes (<3 mm in size) should not be overlooked, and lymph node metastasis to the sigmoid mesentery is rare (see Video, Supplemental Digital Content 1, http://links.lww.com/DCR/A177).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…It has also been reported that the greatest dimension of 45.4% (79 out of 174) resected lymph nodes was below 5 mm . Besides, another study demonstrated that 95 out of 334 (28%) metastatic lymph nodes were less than 3 mm in diameter . In our study, we found that the average quantity of lymph nodes below 5 mm in greatest dimension in the ACN group was significantly more than in the control group.…”
Section: Discussionsupporting
confidence: 73%
“…It has also been reported that the greatest dimension of 45.4% (79 out of 174) resected lymph nodes was below 5 mm . Besides, another study demonstrated that 95 out of 334 (28%) metastatic lymph nodes were less than 3 mm in diameter . In our study, we found that the average quantity of lymph nodes below 5 mm in greatest dimension in the ACN group was significantly more than in the control group.…”
Section: Discussionsupporting
confidence: 73%
“…However, differentiation of stage T2 tumors from stage T3 tumors is challenging as the peritumoral inflammatory reaction tends to mimic tumor penetration through the muscular rectal wall . In addition, preoperative detection of nodal involvement is another challenge in patients with normal‐sized positive lymph nodes . Therefore, improved techniques for clinical staging and risk stratification are key imperatives.…”
mentioning
confidence: 99%
“…Previous studies measuring LN diameters in colorectal cancer by a microscopic method reported that the average sizes of metastatic LN were 3.9-6.9 mm and that of nonmetastatic LN were 2.2-4.5 mm (11)(12)(13)(14)(15)(16). The proportion of metastatic LN 5 mm and smaller was reported to be 45.4%-70.3% and the proportion 3 mm and smaller was reported to be 11.3%-28%; the proportion of LNmetastatic patients having only metastatic LN 3 mm and smaller was reported to be 1.3%-4.1% (10)(11)(12)14,(17)(18)(19). In this study, LN sizes were measured macroscopically.…”
Section: Discussionmentioning
confidence: 99%